Tingkat Kepuasan Konsumen Rumah Kopi Berkat Di Kecamaan Kawangkoan Utara Kabupaten Minahasa - Watuseke, Andre Pinontoan Fadli; Waney, Nordy Fritsgerald Lucky; Lumingkewas, Jelly Ribka Danaly (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to analyze the level of customer satisfaction at Rumah Kopi Berkat, North Kawangkoan District, Minahasa Regency. The research was conducted in August-September 2023 using a mixed approach of primary and secondary data. Primary data was obtained through field observations, interviews with the owner, employees, and consumers, as well as distributing questionnaires to 30 consumer respondents. Secondary data was sourced from related literature such as articles, journals, and internet sites. The analysis was carried out descriptively quantitatively by calculating the customer satisfaction index (CSI). The results showed that the level of customer satisfaction was 83.11% (satisfied category), with the highest assessment on product, price, place, and service variables (satisfied category), while the promotion variable received a fairly satisfied assessment. These findings indicate that Rumah Kopi Berkat has fulfilled consumer expectations in general, but an improved promotional strategy is needed to optimize business attractiveness